Avaliação da atividade citotóxica e antimalárica de análogos da cloroquina - Anna Caroline Campos Aguiar (2011)
Human malaria, according to World Health Organization (WHO), remains the most important parasitic disease and a major public health problem. Their control remains difficult due to resistance of mosquitoes to insecticides, the lack of an effective vaccine, and, especially, the emergency and spread of resistant parasites to most available antimalarial drugs. The specific drug treatment remains a major strategy to reduce morbidity and mortality due to malaria. In this study, chloroquine-analogues in complex with metals were evaluated considering that such association to be believed to represent a promising strategy in the search for new drugs. Seven new analogues were evaluated: (i) in vitro for their activity against P. falciparum; (ii) for their toxicity against human erythrocytes and two cell lines, HepG2 (hepatoma) and BGM (a monkey basal kidney cells); (iii) in vivo against P. berghei; (iv) for possible interactions between the analogous and dimeric hematin in vitro; and, (v) through a molecular docking model, targeting the dimeric hematin. All chloroquine analogs showed intense in vitro anti-Pfalciparum activity (IC50 between 0.04 and 0.55 nM) as measured in animmunoenzimatic test using monoclonals to a parasite histidine rich protein (HRPII) and through radiotopic hypoxanthine incorporation. Some of these analogues were more active than chloroquine and none of them were cytotoxic to HepG2 and BGM cells or caused haemolysis to normal human erythrocytes. Like chloroquine, the chloroquine analogs inhibited heme polymerization in the in vitro as well as in the docking test. Inaddition, two of the compounds tested against P. berghei in experimentally infected mice caused a significant reduction of parasitemia. Taken together, the analogues evaluated in this study represent promising molecules and act on a crucial point for theparasite, by inhibition of hemozoine formation